Advances in credit risk modeling and management - Frédéric Vrins (MDPI, 2020)
Credit risk remains one of the major risks faced by most financial and credit institutions. It is deeply connected to the real economy due to the systemic nature of some banks, but also because well-managed lending facilities are key for wealth creation and technological innovation. This book is a collection of innovative papers in the field of credit risk management. Besides the probability of default (PD), the major driver of credit risk is the loss given default (LGD). In spite of its central importance, LGD modeling remains largely unexplored in the academic literature. This book proposes three contributions in the field.
Keywords: 330; Kreditrisiko; Wohlfahrtsanalyse; Innovation; Risikomanagement